Risk factors associated with household transmission of SARS‐CoV‐2 in Negeri Sembilan, Malaysia - Ng, David Chun‐Ern; Tan, Kah Kee; Chin, Ling; Cheng, Xiang Lin; Vijayakulasingam, Thalitha; Liew, Damian Wen Xian; Zainol Abidin, Nor Zanariah; Lee, Ming Lee; Ganasegeran, Kurubaran; Khoo, Erwin Jiayuan (Journal of paediatrics and child health, 2022)
Aim Households are a significant venue for the transmission of SARS‐CoV‐2. We conducted a study to characterise the transmission dynamics and identify risk factors for household transmission of SARS‐CoV‐2 in Negeri Sembilan, Malaysia. Methods This retrospective observational study included 185 families of paediatric COVID‐19 cases from 1 February 2020 to 31 December 2020. We identified the index case for each household and gathered the socio‐demographic, epidemiological investigation results and risk factors for household transmission from medical case records. The secondary attack rate was calculated, and logistic regression analyses were used to identify risk factors associated with secondary household transmission of SARS‐CoV‐2. Results Of the 848 household contacts, 466 acquired secondary infections, resulting in a secondary attack rate of 55%. The median age of the secondary cases was 12 years. Female household contacts and household contacts who slept in the same room with the index case were significantly associated with increased risk for COVID‐19. Other independent risk factors associated with higher transmission risk in the household included an index case who was symptomatic, a household index case aged greater than 18 years and a male household index case. Conclusions High rates of household transmission of COVID‐19 were found, indicating households were a major setting of transmission of SARS‐CoV‐2. Our data provide insight into the risk factors for household transmission of SARS‐CoV‐2 in Malaysia.